2019
DOI: 10.1523/jneurosci.0990-19.2019
|View full text |Cite
|
Sign up to set email alerts
|

The p75NTR Influences Cerebellar Circuit Development and Adult Behavior via Regulation of Cell Cycle Duration of Granule Cell Progenitors

Abstract: Development of brain circuitry requires precise regulation and timing of proliferation and differentiation of neural progenitor cells. The p75 neurotrophin receptor (p75NTR) is highly expressed in the proliferating granule cell precursors (GCPs) during development of the cerebellum. In a previous paper, we showed that proNT3 promoted GCP cell cycle exit via p75NTR. Here we used genetically modified rats and mice of both sexes to show that p75NTR regulates the duration of the GCP cell cycle, requiring activatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 50 publications
3
15
0
Order By: Relevance
“…Recent evidence has suggested that signalling through the p75 neurotrophin receptor and Bone Morphogenetic Protein (BMP) pathways regulate cell cycle exit of granule progenitors. While removal of the p75 receptor elicits corresponding phenotypes of delayed cell cycle exit and larger cerebella (Zanin et al, 2016(Zanin et al, , 2019, the functions of the BMP pathway in cerebellar development have proved complex.…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence has suggested that signalling through the p75 neurotrophin receptor and Bone Morphogenetic Protein (BMP) pathways regulate cell cycle exit of granule progenitors. While removal of the p75 receptor elicits corresponding phenotypes of delayed cell cycle exit and larger cerebella (Zanin et al, 2016(Zanin et al, , 2019, the functions of the BMP pathway in cerebellar development have proved complex.…”
Section: Introductionmentioning
confidence: 99%
“…We and others have previously reported on the expression and function of p75 NTR in developing cerebellar granule neurons (CGNs), the most abundant neuron subtype in the mammalian brain. [9b, 14] In contrast, the specific expression of TRADD in distinct neuronal subpopulations, including CGNs, is not well understood. We therefore assessed whether TRADD is expressed in developing CGNs at early postnatal stages, coincident with the height of p75 NTR expression.…”
Section: Resultsmentioning
confidence: 99%
“…We also identify the functional role of TRADD recruitment to p75 NTR through DD interaction in the regulation of NF-κB signaling and cell survival in developing cerebellar granule neurons (CGNs), a physiologically relevant neuronal subpopulation which development is strongly regulated by p75 NTR signaling. [9b, 14]…”
Section: Introductionmentioning
confidence: 99%
“…During cerebellar development, GC precursors arise from the cerebellar rhombic lip and migrate rostrolaterally in a subpial stream to form the external germinal zone (EGZ) from embryonic day (E) 12.5 to 17 [ 4 , 8 , 9 , 10 ]. GC precursors rapidly proliferate in the EGZ and, after 7–8 divisions (~128–144 h), move radially to their final destination and differentiate into mature GCs [ 11 , 12 , 13 , 14 ]. During this process, sonic hedgehog (SHH), secreted by PCs, promotes proliferation of GC precursors [ 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%